2013
DOI: 10.2147/ijn.s44090
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of silver-polyvinyl pyrrolidone (Ag-PVP) nanoparticles in mouse macrophages infected with live Chlamydia trachomatis

Abstract: Abstract:Chlamydia trachomatis is a very common sexually transmissible infection in both developing and developed countries. A hallmark of C. trachomatis infection is the induction of severe inflammatory responses which play critical roles in its pathogenesis. Antibiotics are the only treatment option currently available for controlling C. trachomatis infection; however, they are efficacious only when administered early after an infection. The objectives of this study are to explore alternative strategies in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 50 publications
2
19
0
Order By: Relevance
“…The effect of nanoparticles on mouse J774 macrophages viability was measured using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) dye reduction assay and the Cell-Titer 96 Cell Proliferation Assay kit (Promega) as described 19 . Absorbance at 570 nm was measured using a microplate reader.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of nanoparticles on mouse J774 macrophages viability was measured using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) dye reduction assay and the Cell-Titer 96 Cell Proliferation Assay kit (Promega) as described 19 . Absorbance at 570 nm was measured using a microplate reader.…”
Section: Methodsmentioning
confidence: 99%
“…Cytokines and chemokines were quantified in cell free-culture supernatants using multiplex ELISA as described 17,1921 . Only those cytokines and chemokines that were statistically significant ( P ≤ 0.05) above the detection limit (3.2 pg/mL) are reported in this study.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study indicated that AgNP exposures alter the population of intestinal microbiota and gut-associated immune responses in rats [ 18 ]. Anti-inflammatory effects of AgNP capped with polyvinlypyrrolidone (PVP) have also been reported in Chlamydia trachomatis infected mouse J774 macrophages [ 19 ]. However, the effects of AgNP on antibacterial human host immune cell responses have not been systematically examined.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Barralet et al showed that the incorporation of copper ions in calcium phosphate scaffolds could enhance the formation of microvessels and wound tissue ingrowth [329]. Silverdoped synthetic materials showed anti-inflammatory activity [330][331][332]. In chapter 6 of this thesis, we observed increasing chondrogenesis in strontium-containing composites in an osteoporotic model.…”
Section: Do Ions Play An Essential Role?mentioning
confidence: 60%
“…The application of trace elements is thus not limited to bone, but also in other fields such as instructing vascularisation [318,329,[348][349][350] and anti-infection [331,351,352]. For example, the antimicrobial silver (Ag) could suppress inflammatory responses [330,353,354] and the doping of Ag in calcium phosphates has shown to reduce the risk of implant-associated infections [331,351,352,355]. It is known that on the one hand inflammatory response is important for the recruitment of osteoprogenitors and activation of osteogenic cytokine secretion [356][357][358], while on the other hand, excessive inflammation as well as severe infection after implantation should be avoided.…”
Section: Ion-containing Materials In Non-osseous Fieldsmentioning
confidence: 99%